Penggunaan BUKU dan Kepemilikan dalam Menganalisis Efisiensi Perbankan di Indonesia - Bintang Andhyka; Chaerani Nisa; Bambang Puwoko (Al Tijarah, 2017)
In December 2016, there are 116 commercial banks in Indonesia. Those banksare divided into few categories. Two of them are commercial banks based onbusiness activity (BUKU) and based on ownership. This research analyzes allcommercial banks that operates between 2012 and 2016 and divide them intotwo categories mention before. The aim of the research is to find out efficiencyscore using SFA method based on those two categories. The result showthat banks in BUKU 3 have the highest efficiency score, followed by BUKU 1,BUKU 4 and BUKU 2. Meanwhile, on ownership category, state owned enterprisebanks have the highest score. It then followed by foreign banks, private.banks, municipal banks and the last one mix ownership banks